Modeling technical change in climate analysis: evidence from agricultural crop damages - Ahmed A.; Devadason E.S.; Al-Amin A.Q. (Springer Verlag, 2023)
agricultural application; agricultural modeling; calibration; climate change; climate conditions; climate effect; cost-benefit analysis; crop damage; environmental policy; optimization; technological change; technology adoption; Pakistan; agriculture; climate; climate change; crop; economics; Pakistan; Agriculture; Climate; Climate Change; Crops, Agricultural; Pakistan